Teachers' technological literacy for ICT integration to implement competence-based curriculum in public secondary schools in Tanzania - Tumaini Kalinga (Academy of Cognitive and Natural Sciences, 2024)
This study investigated teachers' understanding of ICT integration in implementing a competence-based curriculum (CBC) among public secondary schools. Interviews and focus group discussions were used to collect the data from 139 teachers, academic teachers and the head teachers. Simple random and purposive sampling was used to obtain participants. The thematic analysis covers the whole process of data analysis. The study findings revealed that most teachers are aware of the Education and Training Policy and ICT Policy. However, they could not link their teaching practices in the classroom to meet policy goals, 85% of teachers did not integrate ICT as a pedagogical tool in their teaching and learning process, most teachers did not use online assessment, and the most used ICT devices were smartphones, computers and laptops. The study found that most teachers understand the benefit of ICT in implementing a competence-based curriculum. The study recommends aligning our policies and practices, especially in real school environments.